REVITALISASI GOTONG ROYONG: Penguat Persaudaraan Masyarakat Muslim di Pedesaan (Artikel ini dimuat ulang di Jurnal Dialektika Masyarakat : Jurnal Sosiologi Volume 1 No.1 2017) https://jurnal.uns.ac.id/dmjs/article/view/21688 - Muryanti Muryanti (Jurnal Sosiologi Reflektif, 2014)
Gotong royong is one of local wisdom was embedded in Indonesian culture. It be basic tradition in nation and governmentally. This value is should be come basic in our nation. Although we must believe that social-economic and politic were changed this values. Globalization, poverty and politic situations are the main factors. This article describes the important of togetherness, is called gotong royong. It must be revitalization. We must try continued in our nation life